Role of the General Dudget in the Achievement of Sustainable Development: دراسة تحليلية مقارنة للموازنة العامة العراقية (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The traditional method adopted in the preparation of the general budget in Iraq is not consistent with developments in the size specification response and spending and the associated weakness in the size of the amounts earmarked for investment projects which could adversely affect future generations and not to enable them to continue the development, which requires talking to estimate the adoption of style public expenditure in the state budget and reduce waste and extravagant where and invest public revenues of the state in investment projects and preservation of the environment and natural resources in order to ensure the benefit of future generations system, according to the system serves to achieve the overwhelming majority of members of the community standard of a decent life contribute to solving the problems of unemployment, poverty, ignorance and disease from through attention to investment projects that ensure a lasting increase in the average per capita income, by leaving the traditional budget and a shift to budget programs, performance and design able to achieve the objectives to be achieved, or zero budget in order to identify any of the software programs should be implemented and which must be stopped and ruled out. The research has come to a set of conclusions was the most important of the following: (The traditional budget unable to provide economic efficiency, especially in regard to planning and performance so as not to focus on the goals, as well as weak interest in investment projects that contribute to solving the problems of unemployment and poverty and to ensure the creation of the energies contribute to Achieve a lasting and continuous increase in average per capita income for a long period of time step first the right direction to achieve sustainable development.) As the researcher to a set of recommendations represented the most important of the following: (Find new sources of income to be in support of the source of the primary variable (oil) in anticipation of sudden price changes, and this will reduce the confusion and the fear of falling oil price, as well as activating the role of external oversight to monitor the programs and projects when implemented by various ministries and government agencies, and support the internal control in government departments to keep the resources available.